A CRISPR-Cas13a Based Strategy That Tracks and Degrades Toxic RNA in Myotonic Dystrophy Type 1 - Zhang, Nan; Bewick, Brittani; Xia, Guangbin; Furling, Denis; Ashizawa, Tetsuo (Frontiers in Genetics, 2020)
Cas13a, an effector of type VI CRISPR-Cas systems, is an RNA guided RNase with multiplexing and therapeutic potential. This study employs the Leptotrichia shahii (Lsh) Cas13a and a repeat-based CRISPR RNA (crRNA) to track and eliminate toxic RNA aggregates in myotonic dystrophy type 1 (DM1) – a neuromuscular disease caused by CTG expansion in the DMPK gene. We demonstrate that LshCas13a cleaves CUG repeat RNA in biochemical assays and reduces toxic RNA load in patient-derived myoblasts. As a result, LshCas13a reverses the characteristic adult-to-embryonic missplicing events in several key genes that contribute to DM1 phenotype. The deactivated LshCas13a can further be repurposed to track RNA-rich organelles within cells. Our data highlights the reprogrammability of LshCas13a and the possibility of using Cas13a as a means to treat other microsatellite expansion diseases.